2012
DOI: 10.1016/j.jiph.2012.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-resistant Staphylococcus aureus transmission in a low-prevalence healthcare setting

Abstract: In a setting of low MRSA prevalence, CP does not appear to be a useful predictor of nosocomial transmission or incidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Studies in Saudi Arabia have focused on epidemiological trends of MRSA. For instance, Khanfar et al 5 discussed the prevalence, incidence, and possible predictors of MRSA infection, while Eed et al 20 discussed the molecular characteristics of MRSA among hospital isolates. Our study is the first in the region to address the in-hospital features of MRSA patients compared to controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in Saudi Arabia have focused on epidemiological trends of MRSA. For instance, Khanfar et al 5 discussed the prevalence, incidence, and possible predictors of MRSA infection, while Eed et al 20 discussed the molecular characteristics of MRSA among hospital isolates. Our study is the first in the region to address the in-hospital features of MRSA patients compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“… 13 Saudi Arabia and neighboring Gulf countries have observed a wide variety of strains among MRSA cases. 5 , 10 , 11 The Muslim pilgrimages to Makkah and Medina might contribute to the propagation of diverse MRSA strains, as there is evidence of MRSA’s high transmissibility through the respiratory route. 14 In fact, MRSA has been shown to be one of the main organisms that affects the pilgrims and causes them pneumonia.…”
mentioning
confidence: 99%
“…In the present study, we identified 30% of our MRSA isolates (57 of 187) from the hospitalized patients to be CA-MRSA which is on par with previously reported data from retrospective studies (3). The incidence of 30% CA-MRSA is vital in the current context due to an emergence of CA-MRSA isolates in the Middle Eastern countries, especially in the United Arab Emirates (19)(20)(21)(22)(23)(24). With the lack of uniform infection control policies and surveillance programmes in most GCC countries including the UAE, there is an increased likelihood of local and regional CA-MRSA dissemination in healthcare facilities (21).…”
Section: Discussionmentioning
confidence: 99%
“…Analogous with the globally emerging situation, recent studies in the UAE and other Gulf Cooperation Council (GCC) countries such as Saudi Arabia, Qatar and Baharin have reported an increase in the incidence of MRSA, especially CA-MRSA, infections among hospitalized patients in healthcare facilities (19)(20)(21)(22)(23)(24). The present study was conducted to identify CA-MRSA among the total MRSA isolates in the hospitalized patients over a 2-year period from January 2011 to December 2012.…”
mentioning
confidence: 99%
“…A number of studies have focused on exploring the prevalence and risk factors associated with MRSA colonization in the country. These studies highlighted the fact that MRSA is a common cause of healthcare-associated infections in Saudi Arabia, and that it is an increasing threat in the community [ 11 ]. Moreover, they emphasized the need to understand and address the risk factors associated with MRSA colonization.…”
Section: Introductionmentioning
confidence: 99%